2014
DOI: 10.1093/ejcts/ezt641
|View full text |Cite
|
Sign up to set email alerts
|

Thymectomy in myasthenia gravis: proposal for a predictive score of postoperative myasthenic crisis

Abstract: Our model facilitates the stratification of patient risk and prediction of the occurrence of POMC. Moreover, it could help to guide the anaesthesiologist's decision on the duration of intubation. Further studies based on larger series are needed to confirm these preliminary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 20 publications
3
38
0
1
Order By: Relevance
“…7 We diagnosed POMC as previously described, 19 and found that 12.4% of our patients developed POMC. Though no prospective studies have yet studied POMC, numerous retrospective studies indicated that a preoperative myasthenic crisis, more advanced disease, postoperative infection, and higher dose of PYR were risk factors for POMC; the effects of thymoma or ectopic thymus, timing of surgery, higher level of anti-AchR, and blood loss during surgery are controversial.…”
Section: Discussionsupporting
confidence: 52%
“…7 We diagnosed POMC as previously described, 19 and found that 12.4% of our patients developed POMC. Though no prospective studies have yet studied POMC, numerous retrospective studies indicated that a preoperative myasthenic crisis, more advanced disease, postoperative infection, and higher dose of PYR were risk factors for POMC; the effects of thymoma or ectopic thymus, timing of surgery, higher level of anti-AchR, and blood loss during surgery are controversial.…”
Section: Discussionsupporting
confidence: 52%
“…Based on this sequence, the severity of patient disease could be deduced from patient receiving emergency care or being hospitalized. Two recent studies found that unstable myasthenia gravis before surgery, preoperative plasmapheresis, and patients with a history of myasthenic crisis have increased incidence of myasthenic crisis after surgery [34,35]. Patients with these histories might be considered more vulnerable, and this might explain the significant increase in postoperative adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative management with IVIg or PLEX is effective for rapid improvement and is used to reduce perioperative complications including myasthenic crisis after operation . In this study, preoperative management was performed in 4 (40%) patients with MCAVT and 13 (9.6%) patients without MCAVT (Table ).…”
Section: Discussionmentioning
confidence: 99%